2011
DOI: 10.1209/0295-5075/95/68005
|View full text |Cite
|
Sign up to set email alerts
|

Increased flux pinning in YBa 2 Cu 3 O 7−δ thin-film devices through embedding of Au nano crystals

Abstract: We prepared direct-current superconducting quantum interference device (dc-SQUID) gradiometers consisting of a single YBa2Cu3O 7−δ (YBCO) layer on SrTiO3 (STO) bicrystal substrates. The superconducting thin film was modified by embedding crystalline gold nanoparticles. We investigated the growth conditions of these particles as well as their influence on the properties of the YBCO thin film. In our magneto-optical measurements we found that the presence of embedded nano crystals results in a distinct enhanceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…With the Au seed layer thickness used the typical Au particle size is in the range 10 − 40 nm. 8 The area distribution of the Au nanoparticles is quite homogeneous, whereas the concentration within the depth profile varies, as later discussed.arXiv:1401.6295v1 [cond-mat.supr-con] …”
mentioning
confidence: 91%
See 1 more Smart Citation
“…With the Au seed layer thickness used the typical Au particle size is in the range 10 − 40 nm. 8 The area distribution of the Au nanoparticles is quite homogeneous, whereas the concentration within the depth profile varies, as later discussed.arXiv:1401.6295v1 [cond-mat.supr-con] …”
mentioning
confidence: 91%
“…6 Recently, it has been demonstrated that Au nanoparticles, incorporated in YBCO thin films, lead to an increase of T c and the critical current density j c (from 4 · 10 7 A/cm 2 to 6 · 10 7 A/cm 2 at 10 K). 7,8 Since YBCO is superconducting above the boiling temperature of nitrogen this is of special interest for applications. A stronger flux pinning of the vortices at the Au nanoparticles causes a higher j c , which is crucial in order to improve superconducting magnetic field sensors 8,9 as used in dc-SQUID gradiometers.…”
mentioning
confidence: 99%
“…If one cannot avoid vortex penetration into the superconductor in the first place [5], one can suppress vortex motion through pinning the flux lines at inherent or artificial pinning centres. Several efficient techniques are currently known to introduce such artificial pinning centres into thin films of optimally doped high-temperature superconducting YBa 2 Cu 3 O 7−δ (YBCO) [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…This means, for example, a thin film superconducting quantum interference device (SQUID) gradiometer structure can be manufactured where strong pinning in the antenna structures can be combined with grain boundary Josephson junctions with lower critical currents. The combination of both engineering steps would lead to a significant increase in the signal to noise ratio of the device [20].…”
Section: Introductionmentioning
confidence: 99%
“…10 With a transmission electron microscopic (TEM) analysis, it has been shown that the orientation of the gold nanoparticles with their {111} planes is mostly parallel to the substrate surface. 11 A question still completely unanswered covers the role of the spatial distribution and crystallographic orientation of the crystalline nanoparticles play in this context. Procedures using electron backscatter diffraction (EBSD) provide both integral statements about the particle ensemble and local statements on the nanoparticles based on the available resolution.…”
mentioning
confidence: 99%